Karakter Pribadi Mandiri Anak Kedua atau Anak Tengah - Syahru Ramadhan; Sri Nurhayati Selian (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study explores the experiences and independence of middle children through in-depth interviews with three adolescents aged 17-19 years. Findings reveal diverse impacts of middle child syndrome: Informant M reported feelings of neglect and emotional stress due to divided parental attention; Informant N felt valued and useful within the family dynamic; while Informant A experienced a mix of challenges and strengths, excelling as a family mediator. High levels of independence among participants stemmed from parental encouragement, life in a Islamic boarding school environment, and personal challenges that fostered resilience. Overall, middle child syndrome presents difficulties such as reduced attention but also cultivates toughness, adaptability, and interpersonal skills, highlighting its dual-edged nature in shaping adolescent development. Keywords: Middle Child Syndrome, Independence, Family Dynamics, Birth Order, Emotional Neglect. Abstrak Penelitian ini mengkaji pengalaman dan kemandirian anak tengah melalui wawancara mendalam dengan tiga remaja berusia 17-19 tahun. Hasil penelitian menunjukkan dampak beragam dari sindrom anak tengah: Informan M merasa diabaikan dan mengalami stres emosional akibat perhatian orang tua yang terbagi; Informan N merasa dihargai dan berguna dalam dinamika keluarga; sedangkan Informan A mengalami campuran tantangan dan kekuatan, dengan kemampuan unggul sebagai penengah keluarga. Tingkat kemandirian tinggi para partisipan dipengaruhi oleh dorongan orang tua, kehidupan di lingkungan pesantren, serta tantangan pribadi yang membentuk ketangguhan. Secara keseluruhan, sindrom anak tengah menimbulkan kesulitan seperti kurangnya perhatian, tetapi juga menghasilkan ketangguhan, fleksibilitas, dan keterampilan interpersonal, menegaskan sifat gandanya dalam membentuk perkembangan remaja. Kata Kunci: Sindrom Anak Tengah, Kemandirian, Dinamika Keluarga, Urutan Kelahiran, Pengabaian Emosional